Effect of soil solarization on sclerotial viability of Sclerotinia sclerotrum infecting cauliflower (Brassica oleracea var botrytis subvar cauliflora) - Sharma, Prathibha; Zewain, Qais K; Bahadur, P; Sain, S K (The Indian Journal of Agricultural Sciences, 2005)
An experiment was conducted during 2001-2002 to study the effect of soil solarization for different period of time on sclerotial viability of Sclerotinia sclerotioum (Lib.) de Bary collected from infected cauliflower (Brassica oleracea L.var botrytis subvar cauliflora DC.) in field. Solarization of soil during May and June reduced the populations (89.2-98.3%) of S. selerotiorum in soil and ability of sclerotial surviving sclerotia to form apothecia (90.0-98.6%). The greatest reduction (100%) occurred in the top 7.5 cm layer of soil after 8 weeks but significant effects were seen at 15 and 30 cm soil depths after 9 weeks (100.0 and 93.3%) soil solarization. These reductions were due to microbial colonization by Trichoderma harzianum Rifai and T.viride Persoon, and degradation of selerotia weakened by sublethal temperature produced by solarization.